2014
DOI: 10.3390/molecules19079610
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Antiproliferative Effect of Tepary Bean Lectins on C33-A, MCF-7, SKNSH, and SW480 Cell Lines

Abstract: For many years, several studies have been employing lectin from vegetables in order to prove its toxic effect on various cell lines. In this work, we analyzed the cytotoxic, antiproliferative, and post-incubatory effect of pure tepary bean lectins on four lines of malignant cells: C33-A; MCF-7; SKNSH, and SW480. The tests were carried out employing MTT and 3 [H]-thymidine assays. The results showed that after 24 h of lectin exposure, the cells lines showed a dose-dependent cytotoxic effect, the effect bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…A Tepary bean (Phaseolus acutifolius) lectin fraction (TBLF) has shown differential cytotoxic effects on breast, cervix and colon cancer cell lines as well as on non-malignant cells from the intestinal tract [15,18]. Similar effects were observed with other Tepary bean lectin fractions on different colon cancer cell lines [19,20]. In vivo studies have reported that TBLF (50 mg/kg by intragastric administration for six weeks every third day) exhibits low toxicity, good tolerability and activates the immune system [21,22].…”
Section: Introductionmentioning
confidence: 91%
“…A Tepary bean (Phaseolus acutifolius) lectin fraction (TBLF) has shown differential cytotoxic effects on breast, cervix and colon cancer cell lines as well as on non-malignant cells from the intestinal tract [15,18]. Similar effects were observed with other Tepary bean lectin fractions on different colon cancer cell lines [19,20]. In vivo studies have reported that TBLF (50 mg/kg by intragastric administration for six weeks every third day) exhibits low toxicity, good tolerability and activates the immune system [21,22].…”
Section: Introductionmentioning
confidence: 91%
“…Lectins have the ability to recognize typical sugars constituted on the surface of animal cells and to agglutinate red blood cells (Liener, ). Lectins can also be internalized by cells, where they can trigger a wide variety of signals (Valadez‐Vega et al., ). As a result, lectins have been used for a variety of clinical purposes, including histopathology, immunology, glycoprotein characterization, transformation, and cell inhibition (Valadez‐Vega et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Lectins can also be internalized by cells, where they can trigger a wide variety of signals (Valadez‐Vega et al., ). As a result, lectins have been used for a variety of clinical purposes, including histopathology, immunology, glycoprotein characterization, transformation, and cell inhibition (Valadez‐Vega et al., ). Notably, tumor cell surfaces vary in glycoconjugate composition, compared to normal cells (Hassan, Rouf, & Tiralongo, May, & Tiralong, ).…”
Section: Resultsmentioning
confidence: 99%
“…CaSki cells correspond to a metastatic focus of epidermoid cervical carcinoma, located in the small intestine, and contain 600 copies of HPV16 DNA, which are integrated into its genome. This viral genotype is of high oncogenic risk and is more prevalent in CC cases, while C33A cells correspond to cervical carcinoma, are negative to HPV and highly proliferative 41 , and have both metastastic and invasive capacities 42,43 . The cell line HaCaT was included as a normal control for the system.…”
Section: Methodsmentioning
confidence: 99%